Management of Planning and Organization of Educators at the Ministry of Religious Affairs Bulukumba Regency - Hidayat, Yasysyar; Wahira; Hasan (International Journal of Science and Society, 2025)
This study aims to describe the Management of Planning and Organizing of Educators at the Ministry of Religion, Bulukumba Regency. This research uses a qualitative approach, with data collected through interviews, documentation, and observation. The data analysis technique involves four stages: data collection, data reduction, data presentation, and conclusion drawing. The results of the study indicate that the planning of educators is carried out systematically based on regulations, through needs analysis based on the number of students and class capacity. School principals propose the need for educators to the Ministry of Religious Affairs in Bulukumba Regency, which is then mapped and assigned by the Ministry of Religious Affairs of the Province in coordination with the Ministry of Religious Affairs of Bulukumba Regency. As for the organizing of educators at the Ministry of Religious Affairs in Bulukumba Regency, it has been carried out with a very structured and systematic procedure, involving various stakeholders such as school principals, madrasah supervisors, and the personnel division. This organizing process includes placement, mutation, rotation, and attendance management, all based on educational needs and applicable policies.